2012
DOI: 10.1021/la303328p
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peptide and Guest Charge on the Structural, Mechanical and Release Properties of β-Sheet Forming Peptides

Abstract: The effect of peptide charge on the self-assembly, gelation behavior, and model drug release profiles has been explored here for three octa-peptides, VEVKVEVK (VEK2), VKVKVEVK (VEK3), and VEVEVKVE (VEK1), that carry a net charge of 0, +2, and -2 at neutral pH, respectively. Transparent, self-supporting hydrogels were found to form above a critical concentration when the peptide charge modulus was >1 and this was independent of the sign of the charge. TEM, SAXS, and shear rheology revealed that there were no di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 58 publications
(89 reference statements)
7
88
0
Order By: Relevance
“…Although G ′ (ω) was roughly an order of magnitude larger than G ′′ (ω), indicating elastic-dominated behaviour, the two spectra became comparable on lowering the concentration of Ca 2+ , suggesting a reduction in strong ionic matrix bonds and increased fluidity, consistent with fits to a superposition of wormlike chains [29]. Broadly similar spectra have been observed in a range of polymeric gels, including peptide fibrils [74], block copolymers [77] and intermediate filaments [56]. F pilus producing E. coli biofilms, but not curli producing ones, have also been compared to actin protein gels based on active microrheology experiments [37].…”
Section: Bulk Rheologysupporting
confidence: 68%
“…Although G ′ (ω) was roughly an order of magnitude larger than G ′′ (ω), indicating elastic-dominated behaviour, the two spectra became comparable on lowering the concentration of Ca 2+ , suggesting a reduction in strong ionic matrix bonds and increased fluidity, consistent with fits to a superposition of wormlike chains [29]. Broadly similar spectra have been observed in a range of polymeric gels, including peptide fibrils [74], block copolymers [77] and intermediate filaments [56]. F pilus producing E. coli biofilms, but not curli producing ones, have also been compared to actin protein gels based on active microrheology experiments [37].…”
Section: Bulk Rheologysupporting
confidence: 68%
“…Charged PNFs can repel each other minimizing the aggregation in the system. Roberts et al 24 have shown that for b-sheet forming peptides the net charge of the system, or charge modulus, has to be greater than 1 so that the electrostatic repulsion can prevent fiber aggregation, independent of the sign of the charge. The choice of making the system positively charged rather than negatively charged was based on the consideration that most of the nanoparticles designed for intracellular delivery purposes should be positively charged, to favour the interaction with the moderately negatively charged cell surfaces.…”
Section: Ivis Imagingmentioning
confidence: 99%
“…These include their use as scaffolding for 3D cell cultures, tissue engineering and regenerative medicine as well as their use as vehicle for localised drug delivery 1, 2, 3, 4, 5, 6. Peptide hydrogels are made of short synthetic peptides composed of either natural or nonnatural amino acids that are designed to self‐assemble into higher biomimetic structures.…”
Section: Introductionmentioning
confidence: 99%